THE BRAND EQUITY STRATEGIC MODEL DEVELOPMENT OF THAI ORGANIC RICE - Piluk, Patchara; Rojanasang, Chow; Soonthonsmai, Vuttichat (Journal of Buddhist Anthropology, 2021)
The objectives of this article were to: 1) to examine brand awareness brand association, brand perceived quality, marketing strategy and brand equity and 2) to develop the brand equity strategic model of Thai organic rice.to develop the brand equity strategic model of Thai organic rice. Mixed methods was a research approach in this study. The population consisted of participants who consumed organic rice in Thailand. The 857 samples in the quantitative research, the researcher employed the multi-stage sampling method. The research instrument utilized to collect germane data was a questionnaire. The techniques of descriptive statistics and structural equation modeling (SEM) analysis were employed. In the qualitative research, relevant data were collected by means of in-depth interviewing of 72 participants. The data collected was analyzed by the content analysis method. Findings were as follows: (1) Brand awareness and brand association had a statistically significant direct and indirect effect on brand equity. Brand perceived quality had no statistically significant direct effect on brand equity; however, it had a statistically significant indirect effect on Brand equity. Market strategy had statistically significant direct effect on Brand equity. (2) Brand equity strategic model of Thai organic rice was relevant to empirical data consist of brand awareness, brand association, brand perceived quality and brand Equity. This particular marketing strategy was hypothesized to have a mediating role. Model to measure different factors in the brand equity strategic model of organic rice was congruent with the empirical data ( 2 = 215.81, df = 75, p=0.000, 2/df = 2.86, CFI = 1.00, GFI = 0.97, AGFI = 0.94, RMSEA = 0.047, SRMR = 0.020).